2015
DOI: 10.3389/fpsyg.2015.00241
|View full text |Cite
|
Sign up to set email alerts
|

Delayed disengagement of attention from snakes in children with autism

Abstract: In the visual search task, it is well known that detection of a tilted straight line as the target among vertical lines that act as distractors is easier than vice versa, and that detection of a snake image as the target among flower images is easier than vice versa. In this study, the degree of such search asymmetry was compared between 18 children with autism and 14 typically developing (TD) children. The results revealed that compared to TD children, children with autism were disproportionally slow when ask… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Firstly, it either takes longer (saccade latency) or, secondly, more saccades (DFR) are needed for ASD children to shift their eyes from the centrally presented angry faces compared to happy or neutral faces. Supportive evidence has also been reported in previous studies with the finding of delayed responses to targets caused by visually frightening distractors [27] and the finding of an increased covert attention to threatening scenes presented for a long time (1250ms) [44]. As an extension to this, the current study itself directly reveals a visual disengagement difficulty for central angry faces at the endogenous attention level in children with ASD.…”
Section: Plos Onesupporting
confidence: 91%
See 1 more Smart Citation
“…Firstly, it either takes longer (saccade latency) or, secondly, more saccades (DFR) are needed for ASD children to shift their eyes from the centrally presented angry faces compared to happy or neutral faces. Supportive evidence has also been reported in previous studies with the finding of delayed responses to targets caused by visually frightening distractors [27] and the finding of an increased covert attention to threatening scenes presented for a long time (1250ms) [44]. As an extension to this, the current study itself directly reveals a visual disengagement difficulty for central angry faces at the endogenous attention level in children with ASD.…”
Section: Plos Onesupporting
confidence: 91%
“…In addition to this, other studies have reported increased attention to negative stimuli in ASD. For example, Isomura, Ogawa, Shibasaki & Masataka [ 27 ] found that ASD children take longer to detect the target when threatening stimuli (snakes) are shown as distractors, indicating that individuals with ASD could have difficulties in disengaging from different types of negative stimuli. The inconsistencies in the results to date demonstrate that paradigms used in previous studies may be unsuitable in their ability to provide accurate and clear measures of both exogenous and endogenous attentional characteristics for emotional information in autism [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous literature on non-social threat bias is mixed. For example, a small study by Isomura, Ogawa, Shibasaki, and Masataka (2015) found that autistic children were comparatively slower at finding flower stimuli from among snake stimuli, suggesting that they had difficulty disengaging from the threatening snake stimuli, while Silani et al (2008) showed activation in anterior insula to unpleasant non-social stimuli in both autistic and non-autistic samples. However, another recent study of young children with familial autism found that those who met diagnostic criteria for autism, but not those who did not, did not show attentional bias associated with threatening, non-social images (Milosavljevic et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…They call his name but he has tuned them out, along with every other stimulus in the room.” Schecklmann et al ( 2008 ) “ Hyperfocusing is not mentioned in DSM-IV [with respect to ADHD], but it is known from clinical work and can be described as intensive concentration on interesting and non-routine activities accompanied by temporarily diminished perception of the environment.” Carver ( 2009 ) “Both research and clinical experience tells us that ADHD Children [sic] can exhibit a type of “ hyperfocus ”—intense concentration and single-minded focus when the activity is very interesting.” Kahl and Wahl ( 2006 ) “The researchers noted that “interest” probably the most frequently experience positive emotion, “is an extremely important motivation in the development of skills, competencies and intelligence”. The motivating power of such “interest” may be most apparent when it is absent, as described in the chronic complaints of many adults with ADDs who report that although they can “hyperfocus” on activities in which they have special interest, they chronically find themselves unable to mobilize effort for tasks in which they do not feel any special immediate interest, even when they are fully aware that their failure to do that uninteresting task may cause significant problems later.” Autism Isomura, Ogawa, Shibasaki, & Masataka, ( 2015 ) “Typically, children with autism are known to… pay abnormal and obsessive attention to detail, and to note and record their environment with exquisite clarity (Casey et al, 2008 ). They are capable of becoming hyper-focused and locked-in on apparently arbitrary subjects of interest, and of sustaining their attention on these subjects for unusually long periods of time…as a result of this internal hyper-focus , it would be more difficult for another person to command the attention of the child with autism, and it would also be more difficult for the child himself/herself to command his/her own attention voluntarily (Posner and Dehaene, 1994 ).” Fein ( 2015 ) “The co-existence of strength and vulnerability encapsulated in these narratives captured essential features of the experience of living with Asperger’s Syndrome—a condition that itself brought valued strengths (the ability to hyperfocus on a topic of interest, strengths in systematic thinking, an occasionally exquisite sensitivity to sensory input) as well as disabilities.” Mayes ( 2014 ) “Unlike most children with ADHD who have difficulty sustaining their focus on anything, children with autism can hyperfocus on activities of interest to them (e.g., spending hours twirling a string, assembling puzzles, drawing the same picture over and over, o...…”
Section: Why Has Hyperfocus Been Forgotten?mentioning
confidence: 99%